New diagnostic technology and hidden pits and fissures caries - Fabrizio Guerra; Marta Mazur; Francesca Rinaldo; Denise Corridore; Daniele Salvi; Debora Pasqualotto; Gianna Maria Nardi; Livia Ottolenghi (Senses and Sciences, 2015)
The accuracy in pits and fissures caries detection is of paramount importance in dental caries primary and secondary prevention. A combination of visual examination and probing is currently the mainstay of occlusal caries diagnosis. Unfortunately, these types of inspection alone may leave a certain number of pit and fissure caries undetected. The Vista Cam iX fluorescence camera (Durr Dental, Bietigheim-Bissingen, Germany) is a novel dental diagnostic tool for quantitative assessment of dental caries with high specificity for carious lesions detection. In the presented cases photographic images, representing the visual diagnostic approach, are applied as integration to VistaCam iX Proof images. A step-by-step sequence of inspection and assessment of operative treatment need is presented in a case of hidden pit and fissure caries on a permanent molar. Based on the reported case, it could be observed that VistaCam iX Proof shows promising results in hidden pits and fissures caries detection and could be considered a non-invasive examination method that facilitate the detection of early lesions and a potential diagnostic aid.